1980
DOI: 10.1126/science.208.4449.1265
|View full text |Cite
|
Sign up to set email alerts
|

Cloned Cauliflower Mosaic Virus DNA Infects Turnips ( Brassica rapa )

Abstract: Cauliflower mosaic virus DNA cloned in the Sal I site of bacterial plasmid pBR322 infects turnip plants. The cloned viral DNA must be excised from the recombinant plasmid to infect, but need not be circularized and ligated in vitro. The cloned viral DNA lacks site-specific single-strand breaks found in DNA obtained directly from the virus. However, these breaks are reintroduced into the viral genome during multiplication of the virus in the plant host.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
33
1

Year Published

1981
1981
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(35 citation statements)
references
References 13 publications
1
33
1
Order By: Relevance
“…5 e, j). Similar results were obtained following the passage of cloned CaMV DNA in plants (Howell et al, 1980).…”
Section: Molecular Cloningsupporting
confidence: 81%
“…5 e, j). Similar results were obtained following the passage of cloned CaMV DNA in plants (Howell et al, 1980).…”
Section: Molecular Cloningsupporting
confidence: 81%
“…Cloned DNA of caulimoviruses is infectious when mechanically inoculated on host plants, after enzymic excision from the cloning vector (Howell et al, 1980;Lebeurier et al,, 1980), Because of the reported similarities between RTBV and caulimovirus DNAs (Jones et al, 1991), mechanical inoculation of cloned RTBV DNA, after suitable restriction enzyme digestions, was tested to see whether it was infectious. Another method of testing infectivity, bombarding rice seedlings with microprojectiles (Klein et al, 1987) coated with RTBV DNA (biolistics) was also tried.…”
Section: Introductionmentioning
confidence: 99%
“…The single break (A1) in the so-catled a-strand, the strand which is transcribed, is taken as the zero point of the conventional restriction map [5]; the two breaks in the complementary fl-strand, A3 and A2, are situated at 0.20 and 0.53 map units, respectively. CaMV DNA from which the discontinuities have been eliminated by cloning in pBR322 is fully infectious but the DNA isolated from the progeny of such infection is once again interrupted [6,7], suggesting that the breaks are essential for completion of the infectivity cycle and that a precise mechanism exists for introducing them into the viral DNA.…”
Section: Introductionmentioning
confidence: 99%